Effects of tetrandrine on contractility of isolated pig coronary artery strips - JIA Ju-fang; GAO Lan-lan; XIA Guo-jin; LUO Qi-fa; FANG Da-chao; JIANG Ming-xing (Acta Pharmacologica Sinica, 2016)
Tetrandrine (Tet) 64μM and verapamil (Ver) 8.4 μM relaxed the contraction of coronary artery strips. It is rreversed by raising the extracellular Ca ++ from 2.7 to 14.4μM. within a certain range (Tet 0.1μM-0.1Mm. Ver 1 Nm-1Μm), the % of relaxation was in proportion to dose. However, Tet and Ver exerted no significant inhibition on the extracellular Ca++ contraction induced by NE. It is probable that Tet and Ver primarily inhibited the potential dependent channel (PDC) and prevented the influx of Ca++ through PDC. Tet 10μM and Ver 0.1μM also inhibited the release of intracellular Ca++ by NE. This showed that Tet and Ver might affect the transport of intracellular Ca++. The relaxant effect of Iso on the coronary strips was not blocked by Tet and Ver. Tet is therefore considered to be different from the β-blocker propranolol, but similar to the calcium antagonist Ver.